Evaluation of interfaced plate parameters on impact-based piezoelectric power generation - Ng, Xue Yan; Basari, Amat Amir; Kok, Swee Leong; Ahmad Nawir, Nur Amalina; Seiji, Hashimoto (Penerbit Universiti, UTeM, 2018)
Generally, the piezoelectric will be hit directly for the impact-based piezoelectric energy harvesters to obtain the output voltage and power. A different approach is utilized to demonstrate and evaluate the effect of the interfaced plate on the impact-mode piezoelectric energy harvesting system in this paper. The purpose of this study is to characterize the influence of the interfaced plate on the output efficiency of such a harvester to enhance its performance. The concept is based on the energy absorbed by the interfaced plate after impacted by a ball and spread the energy equally on the piezoelectric disc to harvest electrical charges. Besides that, the penetrated depth of the piezoelectric disc which is caused by the interfaced plate, will stretch the piezoelectric and yield electrical charges. The interfaced plate is attached on top of the piezoelectric disc. A free fall experiment has been conducted to evaluate the performance of the piezoelectric by changing the force with a different value of ball mass and height dropped. There are two parameters of the interfaced plate that will be investigated: diameter of the interfaced plate and height of the interfaced plate. When the diameter of the interfaced plate is decreased, the amplitude of the output power of the piezoelectric disc is expected to be increased. While when the height of the interfaced plate is decreased, the amplitude of the output power of the piezoelectric disc is expected to be increased. These statements have been proven and validated in this paper. However, for the instantaneous impact force (free fall experiment), the output power of the piezoelectric disc without an interfaced plate is higher than the output power of the piezoelectric disc that attaches to the interfaced plate.